Effects of columbite/tantalite (COLTAN) mining activities on water quality in Edege-Mbeki mining district of Nasarawa state, North Central Nigeria - Isah, Mohammed Engha (2021)
The results of the water quality assessments show that the water samples were contaminated with alarming levels of Pb, Cd and Ni. Mean concentrations were Ni (0.008 mg/L), Mn (0.087 mg/L), Pb (0.324 mg/L), Cd (0.029 mg/L), and Fe (0.839 mg/L) in Edege-Mbeki groundwater, while the surface water (mining ponds) had Ni (0.102 mg/L), Mn (0.099 mg/L), Pb (0.358 mg/L), Cd (0.025 mg/L), and Fe (6.99 mg/L). The groundwater samples in Mararaban-Edege which served as the control site had mean concentration levels of Ni (0.032 mg/L), Mn (0.096 mg/L), Pb (0.122 mg/L), Cd (0.039 mg/L), and Fe (0.608 mg/L). The range of pH was found to be from 5.6 ± 0.02 to 6.5 ± 0.12, turbidity was between 39.27 ± 0.29 and 2271 ± 0.00 NTU, and conductivity ranged from 39.27 ± 0.29 to 757.33 ± 5.69 μS/cm, TDS from 25.0 ± 2.3 to 450.67 ± 6.03 mg/L while dissolved oxygen (DO) values from 3.1 ± 0.3 to 3.5 ± 0.3 mg/L.